Measuring the Impact of Covid-19 Pandemic and the Russian Ukrainian War on Dry Bulk Freight Market - Zaid Shaker Abuhamour; Ahmed Ismail Ahmed Hafez (Maritime Research and Technology)
Covid-19 pandemic stands as a monumental disaster in human history, reshaping the global landscape and profoundly impacting various sectors of human life, most notably the world economy. The pandemic's repercussions were felt acutely, resulting in significant disruptions marked by the variation of demand and supply and the effect on the supply chain. Furthermore, the conflict arising from Russia's invasion of Ukraine instigated a new global economic crisis, particularly in Europe. This war exerted a substantial toll on global economic growth, further compounded by the lingering consequences of the Covid-19 pandemic.